High expression of antiviral proteins in mucosa from individuals exhibiting resistance to human immunodeficiency virus (2015)
ABSTARCT: Several soluble factors have been reported to have the capacity of inhibiting HIV replication at different steps of the virus life cycle, without eliminating infected cells and through enhancement of specific cellular mechanisms. Yet, it is unclear if these antiviral factors play a role in the protection from HIV infection or in the control of viral replication. Here we evaluated two cohorts: i) one of 58 HIV-exposed seronegative individuals (HESNs) who were compared with 59 healthy controls (HCs), and ii) another of 13 HIV-controllers who were compared with 20 HIV-progressors. Peripheral blood, oral and genital mucosa and gut-associated lymphoid tissue (GALT) samples were obtained to analyze the mRNA expression of ELAFIN, APOBEC3G, SAMHD1, TRIM5α, RNase 7 and SerpinA1 using real-time PCR. RESULTS: HESNs exhibited higher expression of all antiviral factors in peripheral blood mononuclear cells (PBMCs), oral or genital mucosa when compared with HCs. Furthermore, HIV-controllers exhibited higher levels of SerpinA1 in GALT. CONCLUSIONS: These findings suggest that the activity of these factors is compartmentalized and that these proteins have a predominant role depending on the tissue to avoid the infection, reduce the viral load and modulate the susceptibility to HIV infection.